Pengaruh Brand Ambassador Dan Harga Terhadapkeputusan Pembelian Di Tokopedia (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Noor Salama; N Rachma; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study hopes to decide and elaborate on the impact of brand and cost delivery on purchasing options on Tokopedia. The population in this study is the staff of the business and finance department of the Islamic University of Malang. The data selection technique in this study used a complete survey sample of 90 respondents. The independent factor in this study is the influence of Brand Envoy and Cost then the confidence variable is Buy Choice. The logical method used in this study is a series of direct and driven relapse tests with SPSS 22. The side effects of this concentrate also show that the impact of Brand Representative and Cost is positive and critical to the purchase option. Somehow, brand representation and costs influence purchasing options on Tokopedia. Keywords: Price, Brand Ambassador, and Purchase Decision.